2013
DOI: 10.1186/2162-3619-2-3
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and laboratory characteristics of adolescents with platelet function disorders and heavy menstrual bleeding

Abstract: BackgroundPlatelet function disorders (PFDs) have emerged as an important etiology of heavy menstrual bleeding (HMB) in adolescents. However, neither clinical nor laboratory data have been methodically analyzed in this population subset. The objective of this study was to evaluate these parameters in order to distinguish characteristics of the disorder that in turn will lead to earlier diagnosis and therapy initiation.MethodsRetrospective review of medical records from postmenarcheal adolescents with documente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 39 publications
(86 reference statements)
1
38
1
1
Order By: Relevance
“…Endometrial polyps are the commonest endometrial pathology associated with tamoxifen treatment, with an incidence rate of 8-36% [26]; this frequency is much higher compared with the incidence of 0-11% which is seen in untreated women [27]. Compared with women not taking tamoxifen, these polyps are likely to be larger, more fibrotic and to more frequently show mucinous metaplasia.…”
Section: Polypsmentioning
confidence: 99%
See 3 more Smart Citations
“…Endometrial polyps are the commonest endometrial pathology associated with tamoxifen treatment, with an incidence rate of 8-36% [26]; this frequency is much higher compared with the incidence of 0-11% which is seen in untreated women [27]. Compared with women not taking tamoxifen, these polyps are likely to be larger, more fibrotic and to more frequently show mucinous metaplasia.…”
Section: Polypsmentioning
confidence: 99%
“…Women with PFDs and HMB have been reported to be a clinically distinctive subgroup of women with HMB, with significantly high incidences of blood group O and the δ-storage pool deficiency with a PFD diagnosed well after menarche. High false negative standard platelet function study results are reported therefore additional diagnostic strategies, such as electron microscopy to detect significantly reduced platelet δ-granule numbers should be considered [27].…”
Section: Coagulopathymentioning
confidence: 99%
See 2 more Smart Citations
“…However, a larger portion of patients who do not have identifiable genetic mutations are diagnosed with δ‐SPD via qualitative and quantitative platelet evaluations . δ‐SPD is a relatively rare platelet function disorder with only few studies describing laboratory and clinical findings in the pediatric population …”
Section: Introductionmentioning
confidence: 99%